Empirical Evaluation of the Effect of Heat Gain from Fiber Optic Daylighting System on Tropical Building Interiors - C. Munaaim, Muhammad Arkam; Al-Obaidi, Karam M.; Ismail, Mohd Rodzi; Abdul Rahman, Abdul Malek (MDPI, 2014)
A fiber optic daylighting system is an evolving technology for transporting illumination from sunlight into building interiors. This system is a solution developed by daylighting designers to reduce operational costs and enhance comfort. As an innovative technology, fiber optic daylighting systems can illuminate building interiors efficiently compared with other daylighting strategies. However, as a transmission medium in daylighting systems, optical fibers require uniform light distribution in sunlight concentration, which could generate heat. Therefore, this study aims to investigate the effect of heat buildup produced by end-emitting fiber optic daylighting systems in tropical buildings. The applied method adopts a new fiber optic daylighting system technology from Sweden called Parans SP3, with a 10 m cable to be tested in an actual room size under the Malaysian climatic environment, particularly within the vicinity of the main campus of the Universiti Sains Malaysia. Results show that the system generated a temperature of 1.3 °C under average conditions through fiber optic diffusers and increases indoor temperature by 0.8 °C in a 60 m3 room. According to the results, applying fiber optic daylighting systems, as renewable energy sources, generates extra heat gain in building interiors in the tropics.